A refractory inclusion with solar oxygen isotopes and the rarity of such objects in the meteorite record. (27th March 2020) - Kööp, Levke; Nagashima, Kazuhide; Davis, Andrew M.; Krot, Alexander N.
Abstract: NASA's Genesis mission revealed that the Sun is enriched in 16 O compared to the Earth and Mars (the Sun's Δ 17 O, defined as δ 17 O–0.52×δ 18 O, is –28.4 ± 3.6‰; McKeegan et al. 2011). Materials as 16 O‐rich as the Sun are extremely rare in the meteorite record. Here, we describe a Ca‐Al‐rich inclusion (CAI) from a CM chondrite that is as 16 O‐enriched as the Sun (Δ 17 O = –29.1 ± 0.7‰). This CAI also has large nucleosynthetic anomalies in 48 Ca and 50 Ti (δ‐values are –8.1 ± 3.3 and –11.7 ± 2.4‰, respectively) and shows no clear evidence for incorporation of live 26 Al; ( 26 Al/ 27 Al)0  = (0.03 ± 0.11) × 10 –5 . Due to their anomalous isotopic characteristics, the rare CAIs consistent with the Genesis value could be among the first materials that formed in the solar system. In contrast to the CAI studied here, the majority of CAIs formed in or interacted with a reservoir characterized by a Δ 17 O value near –23.5‰. Combined with 26 Al‐ 26 Mg systematics, the oxygen isotopic compositions of FUN (fractionation and unidentified nuclear effects), UN, and normal CAIs suggest that nebular conditions were favorable for solids to inherit this value for an extended period of time. Many later‐formed materials, such as chondrules, planetesimals, and terrestrial planets, formed in reservoirs with Δ 17 O near 0‰. The distribution could be easier to explain if the common CAI value of –23.5‰, which is consistent with the Genesis value within 3σ, represented the average composition of the protoplanetary disk.